Precipitation-type discrimination and changes in related climate indices in the upper Heihe River Basin during 1960–2021 - Wang, Guanxing; Zhang, Fan; Wang, Li; Zeng, Chen; Shi, Xiaonan; Xiao, Xiong (Frontiers in Environmental Science, 2023)
Precipitation in the upstream region of the Heihe River basin (UHRB) in the northeastern of the Tibetan Plateau, which is the main water source of the basin, has undergone drastic changes in recent decades. In addition to the amount of precipitation, the type of precipitation has a substantial impact on hydrological processes. In this study, we compared the results from three methods (T3.6_4.5, T4.5 and Ding’s method) aimed at improving precipitation type estimation based on daily precipitation type records for 24 discontinuous years. The probability of detection (POD) values of the three methods were 1.9%, 10.3%, and -6.9%, respectively, indicating that the estimation using the T3.6_4.5 method was closest to actual records. Based on the precipitation type distinction, we examined the spatial and temporal changes in the total precipitation, rainfall, snowfall and air temperature at the six stations as well as the spatial average of the UHRB during the past 62 years. We also analyzed changes in the quantity, duration magnitude, and frequency of extreme precipitation using the RClimDex model and statistical analysis. The results showed that rainfall accounts for an average of 81.9% of the total precipitation received in a year. In the context of large scale climate warming, temperatures at all six stations increased significantly, but precipitation changes were only apparent at about half of the stations which were located in regions of high elevation and influenced by both ENSO and the East Asian monsoon. Analysis of the spatial averages in the UHRB revealed that the annual drought events (CDD) were significantly alleviated, and that the growing season length (GSL) was significantly extended. The annual total precipitation, rainfall, and extreme precipitation indices (P99P, P95P, R95P and SDII) increased in magnitude, and the frequency of extreme precipitation events (R10mm) also significantly increased. The findings of this study indicate that under the background of climate warming, the changes of precipitation patterns in the UHRB which may have resulted in bringing better vegetation growth, but also the increasingly frequent extreme rainfall events may pose challenges to growing extreme rainfall events to agriculture and other human activities in local and downstream areas.